Political costs and earnings management: evidence from Tunisia. Issue 4 (7th November 2016) - Ben Rejeb Attia, Mouna; Lassoued, Naima; Attia, Anis
Abstract : Purpose: The purpose of this paper is to test the political costs hypothesis in emerging economies characterized by interventionist governments and weak protection of property rights. The paper uses executives' political connection and state control to measure firms' political costs. Design/methodology/approach: Based on a sample of Tunisian firms, univariate and multivariate analyses are used to test whether firms' political costs have any impact on earnings management. Findings: The empirical analysis indicates that the executives' political connection is not directly related to earnings management. However, the interaction between executives' political connection and the state control affects the firm's sensitivity to political pressure and its earnings management practices. More specifically, this study provides evidence that non-connected firms and state-controlled firms attempt to use accounting policies to decrease their earnings especially during periods of the former government when they had to face high political costs. This finding is robust to comparing means of political cost indicators between different groups. Indeed, private firms with political connection enjoy a significantly lower insurance right, tax and donations and grants compared to other firms. Research limitations/implications: This study provides empirical evidence for the specific application of accounting theory in emerging economies. Practical implications: Political influence may be an important criterion that will be used by auditors and investors to appreciate and detect specific manipulations of accounting earnings. Similarly, regulators should be aware of the political factors effect on discretionary behavior of managers to provide appropriate rules and standards. Originality/value: The study is a pioneer in proving that a firm's size is not always a suitable measure of its political cost. It extends the accounting literature on the role of political economy in the application of the political costs hypothesis. This hypothesis is confirmed in emerging economies by providing new and significantly measure of firms' political costs